2014
DOI: 10.1007/s10867-014-9356-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of molecular chirality due to chiral interactions in a biological environment

Abstract: We explore the interplay between tunneling process and chiral interactions in the discrimination of chiral states for an ensemble of molecules in a biological environment. Each molecule is described by an asymmetric double-well potential and the environment is modeled as a bath of harmonic oscillators. We carefully analyze different time-scales appearing in the resulting master equation at both weak-and strong-coupling limits. The corresponding results are accompanied by a set of coupled differential equations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…The simplest model arises when the odorant is treated as a point dipole inside a uniform and spherical protein surrounded by a uniform polar solvent. For a Debye solvent and a protein with a static dielectric constant, the spectral density is Ohmic with Drude-form cut-off as refs 39 and 40 with and where b is the radius of the protein containing the odorant, Δ μ is the difference between the dipole moment of the odorant in the ground and excited states, is the dielectric constant of the protein environment, and are the static and high-frequency dielectric constants of the solvent, and λ D is the Debye relaxation frequency of the solvent. For an odorant in the aqueous environment, we have and .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest model arises when the odorant is treated as a point dipole inside a uniform and spherical protein surrounded by a uniform polar solvent. For a Debye solvent and a protein with a static dielectric constant, the spectral density is Ohmic with Drude-form cut-off as refs 39 and 40 with and where b is the radius of the protein containing the odorant, Δ μ is the difference between the dipole moment of the odorant in the ground and excited states, is the dielectric constant of the protein environment, and are the static and high-frequency dielectric constants of the solvent, and λ D is the Debye relaxation frequency of the solvent. For an odorant in the aqueous environment, we have and .…”
Section: Resultsmentioning
confidence: 99%
“…For a molecule confined in the double-well potential, we have shown that if the chiral interactions induced by a condensed biological environment are strong enough they can suppress the tunneling process and freeze the molecule in its initial state (see Fig. 7 ) 40 , 47 .
Figure 7 The dynamics of the right-handed state of the open chiral molecule in the aqueous bath at fixed tunneling frequency ω x = 10 −3 for ω z = 10 −5 (blue), ω z = 10 −4 (orange) and ω z = 10 −3 (green).
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Harris and Stodolsky demonstrated, the relevant dynamics of chiral states samples the velocity distribution of the gas molecules, which is strongly temperature-dependent [21,22]. Starting from a microscopic model of the collisions with the gas particles, we derive the spectral density (32) where X(t) is the interaction-picture position operator of the environmental particles. Note that for simplicity we drop all normalization factors expressed by 2π.…”
Section: Dilute Environmentmentioning
confidence: 99%
“…The position operator of the environmental particles can be expanded as [45] X = d 3 r a(r)ρ E (r) (33) where a(r) is the interaction function and ρE (r) is the difference between the gas density operator ρ E (r) and its time-averaged value, assumed to be the uniform gas density ρ. If we substitute (33) in (32), we have…”
Section: Dilute Environmentmentioning
confidence: 99%